LITERARY CONNECTIONS BETWEEN THE WORKS OF ALISHER NAVAI AND WILLIAM SHAKESPEARE - Usmonova Sevara Sultonovna; Boxodirova Komila Xamidjon qizi (Лучшие интеллектуальные исследования, 2023)
Abstract: This article explores the literary connection between Alisher Navai, a prominent 15th-century Central Asian poet, and William Shakespeare, the renowned English playwright of the 16th and 17th centuries. Despite the geographical and temporal distance between the two, this study highlights the striking similarities in their poetic themes, stylistic devices, and cultural impact.